Compliance, Security and Privacy Issues in the Digital Workplace - Иззатовна , Абдуллаева Зульфия (International Journal of Formal Education, 2024)
Improving the quality of social security and privacy in the digital workplace is one of the key areas of government reforms, and today, when all sectors of the economy are switching to digital format, the digitalization of the public services sector has been taken over by e–government, an Internet portal operating on the basis of an industry service platform, the purpose of which is to increase the efficiency of interaction government agencies, citizens and businesses.